2011
DOI: 10.1111/j.1545-5300.2011.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Outcome‐Based Assessment for Family Therapy Training: The Rochester Objective Structured Clinical Evaluation (ROSCE)

Abstract: This paper addresses a growing need for cost-effective, outcome-based assessment in family therapy training. We describe the ROSCE, a structured, evidence-informed, learner-centered approach to the assessment of clinical skills developed at the University of Rochester Medical Center. The ROSCE emphasizes direct observation of trainees demonstrating clinical competencies. The format integrates both formative and summative assessment methods. It can readily be adapted to a wide variety of educational and trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…OSCEs have also been adapted for non-medical training for use in clinical counseling or psychological programs (Roux et al 2011) and social work programs (Lu et al 2011). Overall, numerous communication skills assessment measures have been developed to examine communication skills during an OSCE (Baig, Violato, and Crutcher 2010;Huntley et al 2012;Jiramaneerat 2009;Lu et al 2011;Nuovo, Bertakis, and Azari 2006;Roux et al 2011; for reviews see: Boon andStewart 1998 andSchirmer et al 2005). Another, less common technique, for evaluating student communication competence during interactions with patients is to train lay-people who follow medical students during clinical rounds (Bergus, Woodhead, and Kreiter 2009).…”
Section: Direct Measuresmentioning
confidence: 98%
See 1 more Smart Citation
“…OSCEs have also been adapted for non-medical training for use in clinical counseling or psychological programs (Roux et al 2011) and social work programs (Lu et al 2011). Overall, numerous communication skills assessment measures have been developed to examine communication skills during an OSCE (Baig, Violato, and Crutcher 2010;Huntley et al 2012;Jiramaneerat 2009;Lu et al 2011;Nuovo, Bertakis, and Azari 2006;Roux et al 2011; for reviews see: Boon andStewart 1998 andSchirmer et al 2005). Another, less common technique, for evaluating student communication competence during interactions with patients is to train lay-people who follow medical students during clinical rounds (Bergus, Woodhead, and Kreiter 2009).…”
Section: Direct Measuresmentioning
confidence: 98%
“…Furthermore, research has demonstrated that communication skills exhibited within an OSCE translate to actual clinical practice when later evaluated, which is a good indication of the usefulness of this method of communication skill training for applied health professionals (Walsh, Bailey, and Koren 2009). OSCEs have also been adapted for non-medical training for use in clinical counseling or psychological programs (Roux et al 2011) and social work programs (Lu et al 2011). Overall, numerous communication skills assessment measures have been developed to examine communication skills during an OSCE (Baig, Violato, and Crutcher 2010;Huntley et al 2012;Jiramaneerat 2009;Lu et al 2011;Nuovo, Bertakis, and Azari 2006;Roux et al 2011; for reviews see: Boon andStewart 1998 andSchirmer et al 2005).…”
Section: Direct Measuresmentioning
confidence: 98%
“…On the same theme in Family Process , Le Roux et al . () described the development of the Rochester objective structured clinical evaluation for assessing family therapy skills based on the direct observation of trainees demonstrating clinical competencies.…”
Section: Training: Competencies For Family Therapistsmentioning
confidence: 99%
“…Another perspective is the comprehensive process‐change framework that emphasizes identifying evidence‐based, multilevel interventions that explain the intricacies of change (Sexton, Ridley, & Kleiner, ). An extension of this trend is developing outcome‐based assessment in which there are empirical measures for determining how these skills are mastered (LeRoux, Podgorski, Rosenberg, Watson, & McDaniel, ). By contrast, some propose (Simon, ) that the most significant therapeutic ingredient is embedded not so much in the specific therapy model used or common core skills identified but in the congruence of fit between the philosophical view of the therapist and the model he/she embraces.…”
mentioning
confidence: 99%
“…assessment in which there are empirical measures for determining how these skills are mastered (LeRoux, Podgorski, Rosenberg, Watson, & McDaniel, 2011). By contrast, some propose (Simon, 2012) that the most significant therapeutic ingredient is embedded not so much in the specific therapy model used or common core skills identified but in the congruence of fit between the philosophical view of the therapist and the model he/she embraces.…”
mentioning
confidence: 99%